K obosnovaniyju prioritetov sotsial'noij podderzki napravlenii naucnyh issledovanij i novyh form celevoj orientirovannosti naucnyh znanii - Ratov, I. P.; Popov, G. I.; Mochenoe, V. P.; Chenik, V. D. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to analyse the new directions of scientific researches and specialists' training which pretend to be supported by social and governmental structures at the contemporary period. On the concentration of the priorities of the departmental scientific planning and the priorities of learning programmes for the higher physical culture learning institutions.